Textbook-Driven Oral Proficiency: Assessing Auto Drill Ngomong Arab Sehari-Hari - Dhia Kurniani; Nurul Hidayah; Jamanuddin Jamanuddin (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
The development of speaking skills (maharah al-kalam) in Arabic is a crucial component of effective communication and successful language acquisition. However, in many educational settings, including SMP Islam Az-Zahra 2 Poligon Palembang, traditional instructional approaches have limited students’ opportunities to actively practice speaking, relying heavily on grammar-translation methods. This study aims to evaluate the implementation and effectiveness of the Auto Drill Ngomong Arab Sehari-Hari textbook in enhancing students’ Arabic speaking skills. Specifically, the study addresses three key objectives: (1) to assess the state of Arabic language instruction prior to the textbook’s implementation, (2) to examine the changes in teaching and learning practices following its adoption, and (3) to measure the effectiveness of the textbook in improving students’ speaking proficiency. The research adopts a mixed-methods approach, combining qualitative data from classroom observations, teacher and student interviews, and document analysis with quantitative data from pre-test and post-test scores. Findings indicate a notable shift toward more interactive and student-centered learning after the textbook's introduction. Quantitatively, students' average speaking performance improved by 29.57 points, indicating a substantial enhancement in their oral proficiency. This study concludes that the Auto Drill Ngomong Arab Sehari-Hari textbook is an effective and practical tool for developing maharah al-kalam, especially in secondary-level Arabic instruction. Its structured, context-based drills provide learners with meaningful opportunities for practice, ultimately contributing to improved communicative competence. These findings have implications for curriculum development, suggesting that targeted drill-based resources can significantly improve language learning outcomes.